Frequency of caesarean section in diabetic vs. non diabetic females undergoing induction of labour at term - Fozia Umber Quraishi, Saima Jabeen, Anum Yousaf, Rukhsana Gulzar, Fozia Umber Quraishi, Saima Jabeen, Anum Yousaf, Rukhsana Gulzar (Journal of Rawalpindi Medical College, 2021)
Introduction: Gestational diabetes mellitus (GDM) is a common complication of pregnancy characterized by glucose intolerance recognized during pregnancy. Gestational diabetes is associated with adverse maternal and fetal outcome. Majority of patients with diabetes had induction of labour at term (≥37weeks) to prevent maternal and fetal morbidity especially shoulder dystocia, macrosomia and intrauterine fetal death at term Objectives: To find frequency of gestational diabetes (GDM) in patients undergoing induction of labour. To compare the frequency of caesarean section in diabetic (GDM) and non-diabetic females undergoing induction of labour Methodology: Study Type; It was a descriptive case series conducted at the department of Obstetrics and Gynecology, Shalamar Hospital Lahore. Duration of study was six months after approval from IRB. Sample size; Sample size of 214 cases undergoing induction of labour at term during study period; calculated with 95%confidence level and 3.4% margin of error and taking expected percentage of GDM is 6.9%. Sampling Technique; purposive sampling Methodology: 214 females who will fulfill the inclusion criteria were enrolled in the study from labour room of Department of Obstetrics and Gynecology, Shalamar Hospital Lahore. Induction of labour done with tab prostin 3mg single dose and patients having gestational diabetes were identified and frequency of caesarean section in Diabetic and non-diabetic calculated. Results: In current study, mean age of the patients was 27.8±4.4 years. Mean gestational age was 37.1±3.8 weeks and mean BMI was 28.6±4.1 kg/m2. Primigravida were 88 (41.1%) and multigravidas were 126 (58.9%). Gestational diabetes was found to be in 36 patients (16.8%). Caesarean section was performed in 77 patients (36%). Comparison of frequency of cesarean section in diabetic (GDM) and non-diabetic females undergoing induction of labour revealed majority of the caesarean sections performed in GDM patients (p=0.007). Conclusion In conclusion, our study found a higher incidence of cesarean section than normal delivery in pregnant women with gestational diabetes. Major factors for operational delivery in GDM population included: advanced maternal age and high BMI value.